Concentration induced the interfacial self‐assembly polymorphism of 4, 4′‐dihexadecyloxy‐benzophenon by scanning tunneling microscopy. (25th April 2013) - Xie, Ying; Li, Yijing; Miao, Xinrui
Abstract : The concentration effect on a two‐dimensional (2D) self‐assembly of 4, 4′‐dihexadecyloxy‐benzophenon (DHB) has been investigated by scanning tunneling microscopy. The self‐assembly of DHB at the phenyloctane/graphite interface was concentration dependent. Under low concentration, the DHB molecules were adsorbed intactly on the graphite surface. With the increasing of concentration, one of side chains connecting the conjugated moiety stretched into the liquid phase. The coexistence of two self‐assembled structures was observed in a moderate concentration. The result indicated that the van der Waals interactions between the molecules and the graphite lattice were decreasing with the increasing concentration. After the samples were placed in ambient conditions over 24 h, a different self‐assembled structure was obtained on the gas/solid interface, in which the DHB molecules were adsorbed on the surface with only one of the side chains. Both the benzophenon core and the other side chain were extended to the gas phase. The results demonstrated that concentration played an important role in forming the 2D molecular self‐assembly and provided an efficient approach for the control of the DHB molecular nanostructure. Copyright © 2013 John Wiley & Sons, Ltd.